2022
DOI: 10.1038/s41598-022-09787-5
|View full text |Cite
|
Sign up to set email alerts
|

Dental tissue remineralization by bioactive calcium phosphate nanoparticles formulations

Abstract: Recent health care products are based on formulations claimed to provide enamel remineralization and dentinal tubules occlusion through calcium-phosphate bioactive nanocompounds (ion-doped hydroxyapatite and precursor, amorphous calcium phosphate nanoparticles). This study aimed to characterize, test, and compare for the first time the structure and performance of a representative, market-available sample of remineralizing toothpastes and topical mousses. Formulations were characterized to determine their comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Fluoride ions released from the material can directly inhibit the metabolic pathways of microbial cells in the overlying biofilm and accumulate at the surrounding hard tissue surfaces [30]. The latter leads to the precipitation of calcium fluoridelike deposits, which act as a reservoir and gradually release fluoride during decreased pH conditions [24,31]. The released fluoride prevents enamel demineralization and reduces caries susceptibility by incorporating fluoride into enamel hydroxyapatite via filling or displacing the hydroxyl vacancies, stabilizing the crystal structure forming fluorapatite and lowering the solubility product constant (Ksp).…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride ions released from the material can directly inhibit the metabolic pathways of microbial cells in the overlying biofilm and accumulate at the surrounding hard tissue surfaces [30]. The latter leads to the precipitation of calcium fluoridelike deposits, which act as a reservoir and gradually release fluoride during decreased pH conditions [24,31]. The released fluoride prevents enamel demineralization and reduces caries susceptibility by incorporating fluoride into enamel hydroxyapatite via filling or displacing the hydroxyl vacancies, stabilizing the crystal structure forming fluorapatite and lowering the solubility product constant (Ksp).…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride ions released from the material can directly inhibit the metabolic pathways of microbial cells in the overlying biofilm and accumulate on surrounding hard tissue surfaces [ 34 ]. The latter leads to the precipitation of calcium fluoride-like deposits, which act as a reservoir and gradually release fluoride during decreased pH conditions [ 27 , 35 ]. The released fluoride prevents enamel demineralization and reduces caries susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Three randomly selected micrographs were obtained for each disk (500×, 2000×, and 5000×) for morphological observation of the surface and with the EDS probe (300 × 300 μm fields) in full-frame mode at 150 s acquisition time. The data acquired by EDS were averaged for each specimen and element, representing the wt.% distribution in a ≈1 μm superficial layer (See Ionescu et al, 2022, Figure 6 [ 27 ]). Elemental distribution at the surface level was visually displayed using the map mode (5000×), with an acquisition time of 600 s.…”
Section: Methodsmentioning
confidence: 99%
“…To make ACP-PILP more translatable, groups have evaluated ACP-PILP embedded in dental topical formulations, adhesives, or self-setting materials. An interesting approach developed by Shi et al was based on a mineralized adhesive containing PASP-stabilized PILPs . Here, they showed that ACP-PILPs could be immersed in the etching material with minimal agglomeration and when applied to etched dentin surfaces, they significantly reduced dentin permeability.…”
Section: Cap Delivery Systems For Dentin Regeneration and Biominerali...mentioning
confidence: 99%